Research in social movements, conflicts and change. Vol. 38 - Coy, Patrick G. (Bingley, U.K. : Emerald, 2015)
A long-standing characteristic of the Research in Social Movements, Conflicts and Change series is publishing new theoretical and empirical work that connects previously disparate sub-fields. This volume continues that tradition by opening with five papers that join social movements research with organizational theory, new institutionalism, strategic action fields, and nonviolent action. One study does this by examining how the Fenian Brotherhood organized a transnational revolutionary movement for Ireland's independence. Another paper analyzes the strategic relations between conservative, moderate and radical organizations in different movements, while a further study zeroes in on nonviolent action campaigns. One chapter examines how the North American SlutWalk campaign responded to the organizational field by strategically adapted their framing to make it more resonant transnationally. Other chapters examine how LGBT organizational presence influences the passage of hate crime legislation, and how the women's movement in Franco's Spain persevered through repression and abeyance partly due to cultural practices."
Social movements in abeyance in non-democracies: the women's movement in Franco's Spain / Celia Valiente -- How social movements matter: including sexual orientation in state-level hate crime legislation / Christie L. Parris, Heather L. Scheuerman -- Transnational nationalism: strategic action fields and the organization of the Fenian movement / Howard Lune -- Home is where activism thrives: community setting and persistent protest participation / Sharon S. Oselin -- A quantitative reevaluation of radical flank effects within nonviolent campaigns / Elizabeth Tompkins -- No "shaming this slut": strategic frame adaptation and North American SlutWalk campaigns / Kelly Birch Maginot, Soma Chaudhuri -- Humor, collective identity, and framing in the new atheist movement / Katja M. Guenther, Natasha Radojcic, Kerry Mulligan -- Waves of contention: relations among radical, moderate, and conservative movement organizations / Belinda Robnett, Carol L. Glasser, Rebecca Trammell -- Transnational field and frames: organizations in Ecuador and the US / Beth Williford, Mangala Subramaniam.
Includes bibliographical references.
Print version record
Keywords: Political Science -- Peace; Political activism; Social movements; Social change